Naming is Dominating? : Universalization of theater and epistemic silencing about Afro-Brazilian scenic manifestations - Dumas, Alexandra Gouvêa (Revista Brasileira de Estudos da Presença, 2022)
By considering theater as one of the many scenic manifestations of humanity, this textual digression intends to denaturalize its universalization by placing it in the historical and cultural context of the Brazilian colonization process. Based on studies on epistemic racism and aesthetic racism, it is questioned the excluding centrality of white-western theater used in the reading of the multiple manifestations of scenic character of African matrix gestated and produced in the Brazilian diaspora.